Marketing warhorse - Kumar, Pranav (Universiti Utara Malaysia Press, 2013)
WHAT IS IN THIS BOOK?The attacking strategies observed in today's marketplace.The practices that put the businesses in a tight spot.The practices that big consultants understand, you don't.The real practices that can be learnt only in markets, not at any b-school.The practices that are a bit compromising on ethical aspects and aimed at eliminating you from business.Even in the movie Titanic, the first class passengers ensured to have the ordinary class passengers locked up and to be disembarked only after the elite.That is how the leaders act to maintain their dominance. In market also, leaders and successful companies have such strategies to create and maintain their leadership. Marketing Warhorse will help you identify all such areas wherein you are attacked and where you need to have a sound strategy in place to emerge and stay successful.